Communicating with the aged : impact of government programmes and policies on the caregivers of the elderly. - Ng, Julian Hui Kuan. (2008)
The present study examines the efforts made by the Singapore government in planning and implementing policies, programmes and services for the older people in Singapore and the ways in which they are communicated to the elderly, or their caregivers.